2016
DOI: 10.1111/1471-3802.12344
|View full text |Cite
|
Sign up to set email alerts
|

Português Para Surdos E as Tecnologias Digitais

Abstract: Palavras-chave : ensino de português como L2, português para surdos, tecnologias digitais.Este trabalho visa analisar atividades pedag ogicas propostas por Quadros and Schmiedt (2006) e relacionar a discussões sobre uso de tecnologias digitais no ensino de L ıngua Portuguesa para surdos. Temos como m etodo pesquisa bibliogr afica com selec ßão, leitura e an alise de artigos, peri odicos e livros referentes a utilizac ßão dos recursos tecnol ogicos digitais para ensinar L ıngua Portuguesa para surdos. E como p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
4
0
2
Order By: Relevance
“…La falta de conocimiento de la estructura lingüística de la Lengua de Señas y de la cultura Sorda por el profesor oyente que actúa con alumnos Sordos es un obstáculo en el proceso de enseñanza de la escrita en Lengua Portuguesa (Castro & Calixto, 2016).…”
Section: Discussionunclassified
“…La falta de conocimiento de la estructura lingüística de la Lengua de Señas y de la cultura Sorda por el profesor oyente que actúa con alumnos Sordos es un obstáculo en el proceso de enseñanza de la escrita en Lengua Portuguesa (Castro & Calixto, 2016).…”
Section: Discussionunclassified
“…Turning the focus of this review to the thematic axes (Figure 3), the six studies that make up the first group have the bias that points to the discussion of the teaching and learning process of written PL for the deaf [4][5][6][22][23][24] . In this group, we identified some studies that sought to present didactic strategies that aimed to facilitate the access of the deaf to written LP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this group, we identified some studies that sought to present didactic strategies that aimed to facilitate the access of the deaf to written LP. Among them, three surveys 4,22,23 have used digital information and communication technologies to achieve this goal, namely: digital book 4 , transposition 22 of some activities proposed in a publication by MEC 25 for the digital sphere and augmented reality 23 for the teaching of words. In the research 4 that used a digital book, the authors concluded that, based on the potentialities arising from the technologies, it is believed that it is possible to produce new meanings in the work with the most diverse language practices in the school context; on the other hand, school practices already considered canonical (and widely diffused and questioned), which in many cases end up being merely reproduced in digital media and evidence school doings that differ greatly from the ways in which children and young people (and the teachers themselves) have been reading and writing in non-school contexts by appropriating the most diverse digital resources 4 .…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations